2020
DOI: 10.1016/j.nicl.2019.102140
|View full text |Cite
|
Sign up to set email alerts
|

Reduced forced vital capacity is associated with cerebral small vessel disease burden in cognitively normal individuals

Abstract: HighlightsDecreased FVC (% pred) was associated with increased cerebral small vessel disease burden even in cognitively normal subjects.This reduced lung function was related to low Mini-Mental Status Examination (MMSE) scores in cognitively normal subjects.Path analyses showed that white matter hyperintensities partially mediated the positive relationship between FVC (% pred) and MMSE score.There was no significant association between low FVC (% pred) and cortical thickness in cognitively normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…4c ). Although none were statistically significant after correction for multiple testing, these traits (age of first birth 11 , forced vital capacity 39 , squamous cell lung cancer 40 , and total cholesterol 41 ) were reported in previous studies to correlate with AD. In addition, we estimated overall SNP heritability ( ) to be 0.16 (SE = 0.06) in the Japanese GWAS data, although Lee et al 42 estimated the to be 0.24 (SE = 0.03) in the European GWAS data.…”
Section: Resultsmentioning
confidence: 71%
“…4c ). Although none were statistically significant after correction for multiple testing, these traits (age of first birth 11 , forced vital capacity 39 , squamous cell lung cancer 40 , and total cholesterol 41 ) were reported in previous studies to correlate with AD. In addition, we estimated overall SNP heritability ( ) to be 0.16 (SE = 0.06) in the Japanese GWAS data, although Lee et al 42 estimated the to be 0.24 (SE = 0.03) in the European GWAS data.…”
Section: Resultsmentioning
confidence: 71%
“…Greater pulmonary function measures were significantly protective against CSVD in this study. Reduced FVC 27 , FEV1 28 and chronic obstructive pulmonary disease 29 were previously reported to increase CSVD risk. Reduced midlife lung function was associated with increased WMH in late life.…”
Section: Discussionmentioning
confidence: 90%
“…Two studies have shown that lower FEV1 is related to smaller volumes of gray and white matter and a greater volume of WMH 30,31 . However, another study has indicated that poor FVC, but not FEV1, is associated with increased WMH 29 . To date, no prior studies have addressed the association between PF and cognitive trajectories in different cognitive domains with supporting results from brain MRI data.…”
Section: Narrativementioning
confidence: 99%
“…25 So far, only a few studies have addressed the association between PF and structural brain differences, and with mixed results. [29][30][31] Two studies have shown that lower FEV1 is related to smaller volumes of gray and white matter and a greater volume of WMH. 30,31 However, another study has indicated that poor FVC, but not FEV1, is associated with increased WMH.…”
Section: -19 Years)mentioning
confidence: 99%
See 1 more Smart Citation